Investigation into the effects of salt chemistry and SO2 on the crack initiation of CMSX-4 in static loading conditions - Martinez, Fabian Duarte; Morar, Nicolau I.; Kothari, Maadhav; Gibson, Grant J.; Leggett, Jonathan; Mason-Flucke, Julian C.; Nicholls, John R.; Castelluccio, Gustavo M.; Gray, Simon (Springer, 2020)
Although evidence exists of the potential impact of stress, co-incident with corrosive environments at high temperature, for single crystal turbine blades, the mechanism responsible is not fully understood. This work explores the effect of CaSO4, Na2SO4 and sea salt on the scale formation and crack initiation of CMSX-4 at 550°C in 50 ppm of SO2 and synthetic air under a static stress of 800 MPa. The cross-sectional analysis showed that the CaSO4 and the Na2SO4 salted specimens did not undergo a significant degree of corrosion degradation and no cracks were detected after 400 hours of exposure. However, sea salt caused significant degradation to the scale and cracks were detected by X-ray CT scanning after 400 hours of exposure. The findings from this study suggests that the sulfation of chlorine containing species in sea salt led to the formation, vaporisation and re-oxidation of metal chlorides and this mechanism was found to play a key role in the formation of a non-protective scale. An active oxidation mechanism has been proposed to interpret the results. In conclusion, it is hypothesized that due to the synergistic effect of stress and the formation of a non-protective scale, fast diffusion paths for sulfur, oxygen and chlorine ingress were formed. Further work is currently being undertaken to understand the effect of these species on the local embrittlement of CMSX-4 that ultimately led to the initiation of cracks in the specimen.
This volume is a collection of papers from the 14th International Symposium on Superalloys, held on September 12–16, 2021
Keywords: FactSage 7.3; X-ray computed tomography; Hot corrosion; C-ring; CMSX-4